2011
DOI: 10.1007/s12088-011-0205-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Trichoderma spp. for Antagonistic Activity Against Root Rot and Foliar Pathogens

Abstract: Trichoderma, soil-borne filamentous fungi, are capable of parasitising several plant pathogenic fungi. Twelve isolates of Trichoderma spp. isolated from different locations of South Andaman were characterized for their cultural, morphological and antagonistic activity against soil borne and foliar borne pathogens. The sequencing of these isolates showed seven different species. The isolates revealed differential reaction patterns against the test pathogens viz., Sclerotium rolfsii, Colletotrichum gloeosporioid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 18 publications
6
40
0
7
Order By: Relevance
“…In vitro assay clearly showed that antagonists T. harzianum halted the radial mycelium growth of highly virulent isolate F. oxysporum, R. solani and S. rolfsii, with varying levels of antagonism. Similar antagonistic effect of T. harzianum against these soil-borne pathogens infecting many other crops was also observed by several other investigators (Sundar et (Kumar et al, 2012), and there may be relationship between the production of these enzymes and the ability to inhibit the pathogen (Elad et al, 1982, Sivan andChet, 1989). Results in this study also revealed that the radial mycelial growth of the pathogens was interfered by T. harzianum within the contact area or interface zone.…”
Section: IVsupporting
confidence: 89%
“…In vitro assay clearly showed that antagonists T. harzianum halted the radial mycelium growth of highly virulent isolate F. oxysporum, R. solani and S. rolfsii, with varying levels of antagonism. Similar antagonistic effect of T. harzianum against these soil-borne pathogens infecting many other crops was also observed by several other investigators (Sundar et (Kumar et al, 2012), and there may be relationship between the production of these enzymes and the ability to inhibit the pathogen (Elad et al, 1982, Sivan andChet, 1989). Results in this study also revealed that the radial mycelial growth of the pathogens was interfered by T. harzianum within the contact area or interface zone.…”
Section: IVsupporting
confidence: 89%
“…Em conformidade com o nosso estudo, Adandonon et al (2006) Nesse contexto, uma possível explicação para o alto antagonismo de CEN155, CEN158, CEN169, CEN170, CEN194 e CEN197 contra o fungo S. rolfsii, em detrimento dos demais isolados de T. harzianum, reside no fato de que o conjunto de mecanismos de controle biológico anteriormente citado, pode variar entre isolados de uma mesma espécie, tanto em experimentos in vitro (KUMAR et al, 2012) quanto em experimentos in vivo (MIRANDA et al, 2006). Segundo Louzada et al (2009), não há relatos na literatura que informem sobre a perda de diversidade de Trichoderma spp.…”
Section: Resultsunclassified
“…em condições de campo consiste em prática promissora, uma vez que o controle biológico oferece maior durabilidade, segurança e melhor custo-efetividade do que os fungicidas químicos aplicados no solo (YAQUB; SHAHZAD, 2011;KUMAR et al, 2012). Os agricultores podem usar isolados de Trichoderma efetivos contra S. rolfsii, almejando reduzir perdas no estande inicial e na produção das culturas do feijoeiro e soja, e como conseqüência, incrementar os rendimentos.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Dentre as espécies, T. harzianum e T. asperellum são as mais estudadas, além de outras como T. koningii, T. viride, T. hamatum e T. pseudokoningii. As espécies desse gênero produzem enzimas líticas que causam degradação das paredes celulares dos fungos que hiperparasitam, sendo a produção dessas enzimas diretamente relacionada com a eficácia no processo de hiperparasitismo (KUMAR et al, 2012).…”
Section: Survival Of Resistance Structures Inunclassified